Listen, live and learn: A review of the application process, aiming to enhance diversity within the Listen, Live and Learn senior student housing initiative at Stellenbosch University (Journal of Student Affairs in Africa, 2021)
The Listen, Live and Learn (LLL) initiative at Stellenbosch University (SU) is a senior student housing model with the aim of providing an experiential opportunity for students to make contact with ‘the other’. It is posited on the social contact theory assumption that if people of different genders, races, ethnicities, and/or religions make contact and interact with one another on an equal level, then less stereotyping by them will occur. The initiative therefore aims to enhance interaction between diverse students and to enable social integration. However, as diversity is a core element of LLL, an application and selection process had to be developed in order to provide a holistic, transparent, unbiased and scaleable tool. The present results suggest that the application and selection process, specifically developed for the enhancement of diversity within the LLL initiative, maintained the distribution of race and gender, as constructs of diversity throughout the process. The conclusion can be drawn that the process is holistic, transparent, unbiased and scaleable while providing a practical example of a standardised alternative selection process for programmes seeking to increase diversity.
Keywords: Diversity; student housing; application and selection process; social contact theory; race; gender